2021
DOI: 10.35234/fumbd.900079
|View full text |Cite
|
Sign up to set email alerts
|

Classification of OCT Images via Deep Learning

Abstract: Bu makalede, dünyada görme bozukluklarının %8.7’sinin sebebi olan yaşa bağlı makula dejenerasyonu hastalığının tespit edilmesi için otomatik bir sistem sunulmuştur. Hastalığın teşhisi için, son zamanlarda görüntüden özellik tanısı çıkarma işlemlerinde sıklıkla kullanılan evrişimsel sinir ağı mimarisinden faydalanılmıştır. Çalışmada, yaşa bağlı makula dejenerasyonu hastalığının sınıflandırılması için evrişimsel sinir ağı, etiketli 28031 adet OCT görüntüsü ile eğitilmiştir. Eğitilen evrişimsel sinir ağı 6900 ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(8 reference statements)
0
0
0
Order By: Relevance
“…Age Related Macular Degeneration (AMD) disease was detected using Xception, VGG16, InceptionV3 and ResNet50 deep neural network models trained with Convolutional Neural Network (CNN) architecture [4]. In another study, Tasmin et al, suggested the use of MobileNetV2, ResNet50 and Xception deep neural network models in the classification of normal, Drusen, AMD, Diabetic Macular Edema (DME) of the retina based on CNN architecture using OCT images [5].…”
Section: Güldemir Et Al In Their Study In 2021 Oct-optical Coherence ...mentioning
confidence: 99%
“…Age Related Macular Degeneration (AMD) disease was detected using Xception, VGG16, InceptionV3 and ResNet50 deep neural network models trained with Convolutional Neural Network (CNN) architecture [4]. In another study, Tasmin et al, suggested the use of MobileNetV2, ResNet50 and Xception deep neural network models in the classification of normal, Drusen, AMD, Diabetic Macular Edema (DME) of the retina based on CNN architecture using OCT images [5].…”
Section: Güldemir Et Al In Their Study In 2021 Oct-optical Coherence ...mentioning
confidence: 99%